Remodeling of Aortic Configuration and Abdominal Aortic Branch Perfusion After Endovascular Repair of Acute Type B Aortic Dissection: A Computed Tomographic Angiography Follow-Up - Yuan, Zihui; Li, Yiqing; Jin, Bi; Wang, Jian (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To report aortic remodeling and abdominal aortic branch perfusion pattern after thoracic endovascular aortic repair (TEVAR) for acute Type B aortic dissection (TBAD) and to analyze whether these changes are affected by false lumen (FL) status. Materials and Methods: Between January 2014 and May 2021, all 59 enrolled patients with acute TBAD were treated with TEVAR and had post-operative or follow-up images. Computed tomography angiograms obtained before discharge and at follow-up were compared with baseline scan. The largest diameters of true lumen (TL), FL and transaorta were recorded. FL thrombosis and changes in TL, FL, and transaortic diameters were assessed. Perfusion pattern changes of abdominal aortic branch arteries were characterized. Measurement and analysis were at the stented thoracic, the unstented thoracic, and the abdominal aorta. Results: Mean follow-up was 17.1 months. In the stented thoracic aorta, average TL diameters increased, average FL diameters decreased, and average transaortic diameters did not change; 82.6% of patients had either the stable or shrinking transaortic size and 87% of patients achieved total FL thrombosis. In the unstented thoracic aorta, average TL diameters increased; transaortic growth and no change occurred in 39.1% and 45.7% of patients, respectively, and complete FL thrombosis was in 50% of patients. In the abdominal aorta, average FL and transaortic diameters increased; aorta was expanded in 52.2% of patients; and FL remained patent in 65.2% of patients. Of the 354 branches, 37 branches (10.5%) exhibited changes in perfusion patterns. 22 branches (6.2%) demonstrated increased TL perfusion. 15 branches (4.2%) had increased FL contribution. Compared with patent or partially thrombosed FL, complete FL thrombosis accompanied the bigger decrease in FL diameters, the larger increase in TL diameter, and the higher percentage of abdominal branch TL perfusion. Conclusions: TEVAR stabilized the size of the stented thoracic aorta, with TL expansion and FL obliteration in majority of patients. However, abdominal aortic FL remains patent and expanded with resultant transaortic growth over a long period of follow-up. Perfusion patterns of abdominal aortic branches remain largely stable after TEVAR. Failure to achieve FL thrombosis negatively affect the remodeling of a contiguous abdominal aortic dissection.